Effectiveness and safety of pirfenidone for idiopathic pulmonary fibrosis. Issue 6 (7th May 2019) - Marcos Ribes, Borja; Sancho-Chust, José N; Talens, Amparo; Arlandis, Mar; Herraiz, Paola; Chiner, Eusebi; Aznar, Teresa
Abstract : Objectives: To assess the long-term effectiveness of pirfenidone in idiopathic pulmonary fibrosis (IPF) treatment and to establish its adverse effects profile. Methods: Retrospective observational study in patients with IPF who initiated treatment with pirfenidone between 2011 and 2016. We collected demographic variables (age, sex); date of first and last treatment; reason for discontinuation; pulmonary function measures (forced vital capacity (FVC), carbon monoxide diffusion capacity (DLCO), and 6 min walk test (6MWT)) at treatment initiation (baseline) and at 1, 2 and 3 year follow-up; adherence to pirfenidone treatment; recorded adverse effects; and mortality. Results: Thirty-one patients treated with pirfenidone were included; mean±SD age was 69±8 years, 74% were men, and 59% had a smoking history. Mean baseline values were: FVC 2.43±0.66 L (61.8±12.1%); DLCO 46.1±19.4%; and 6MWT 334±125 m. Median duration of treatment was 14±13 months, and treatment was discontinued in 58% of patients. The most frequently observed adverse effects were gastrointestinal disturbances and photosensitivity. Twenty (65%) patients were evaluated at 1 year, when mean FVC was 2.41±0.86 L (64.7±20.3%); DLCO 50.8±26.8%; and 6MWT 341±139 m. At 2 years' follow-up, 11 patients (36%) who were still taking pirfenidone were evaluated. Mean FVC was 2.34±0.79 L (66.2±14.7%); DLCO 50.0±28.3%; and 6MWT 265±121 m. At 3 years, five patients were still taking the treatment. Mean FVC was 2.71±0.84 L (71.0±24.7%); DLCO 52.6±26.7%; and 6MWT 286±139 m. Nineteen per cent of patients were non-adherent to treatment. Conclusions: Pirfenidone seems to be effective for long-term control of IPF despite substantial variability in response among individual patients. The most frequent adverse effects were digestive and cutaneous, prompting in some cases a reduction in dose or even discontinuation of the treatment.